The Urgency of Reviewing the Revocation of the Sea Sand Export Ban Policy - Tsania Nuha Alfani; Putri Rahmawati; Nelli Noviyani (The Indonesian Journal of International Clinical Legal Education, 2023)
The lifting of the ban on the export of sea sand is a policy that impacts marine ecosystems and coastal communities. Protecting the environment is part of the state's obligation, which is also the right of every citizen. Unwise management of natural resources has a significant impact on environmental balance. In this case, policies regarding natural resource management are in the spotlight in various countries. One of the natural resources currently getting much discussion is resources resulting from marine sedimentation, such as sea sand, which is the main ingredient used in constructing buildings and other infrastructure. The research methodology used is a normative juridical approach. This research aims to determine what regulations are in government regulations regarding the management of marine sedimentation products and the urgency of studying the promulgated policies. The research results obtained by the author are that the Government Regulation on Management of Marine Sedimentation Results, which revokes the Presidential Decree on Control and Supervision of Sea Sand Cultivation, only focuses on the administrative obligations of business actors in managing marine sedimentation products. The government must review the impact of managing marine sedimentation results on environmental sustainability.